Analisis Perbandingan Kinerja Keuangan Perusahaan Telekomunikasi Milik Pemerintah (BUMN) Dan Swasta Yang Terdaftar Di Bursa Efek Indonesia Periode 2007-2011 - Hasan Ismail; Endang Setyawati (BIP's JURNAL BISNIS PERSPEKTIF, 2012)
Theoretically the company in financial management in addition to using their own capital but also the use of external capital, so that the larger the company's capital or a large firm size. With the ever increasing size of the company, the management required to manage existing resources as effectively as possible, thus making a profit (net)are large, this affects the stock demand and further increase the stock price will also increase. Objectives to be obtained in this study is to investigate and analyze the financial performance of significant differences, between Telecommunications Company Owned Enterprises (SOEs) and private-owned telecommunications company that went public and listed on the Indonesia Stock Exchange. Population used in this study is a Telecommunications Company went public and listed on the Indonesia Stock Exchange. While the sample is taken is the profitability ratios such as gross profit margin (GPM), operating profit margin (OPM), net profit margin (NPM), return on assets (ROA), return on equity (ROE) and Earnings per Share (EPS) at Telelomunikasi companies that go public and have complete data in 2007-2011 period is 5 company, a Telecommunication Company of the State Owned Enterprises (SOEs) and Private Telecommunication company 4. The model used is a non-parametric statistics using a different test(Independent Sample Test). These results indicate that thevariable used is the gross profit margin (GPM), operating profit margin (OPM), net profit margin (NPM), return on assets(ROA), return on equity (ROE) and Earnings per Share (EPS) significantly influence the financial performance differences between SOEs and private telecommunications companies that gopublic in the period 2007-2011, and shows the financial performance of state-owned telecommunications company betterthan Private Telecommunications company. In the present study indicate that use of all the variables, the variable ROE on state-owned telecommunications companies stand out and show a better value. ROE on Telecommunications Private companies showed a decline in each year.